The Logic of Hope: Extensions of Kant's View of Religion - Axinn, Sidney, (Value Inquiry Book Series ;, 1994)
This book is a thorough study of the question posed by Kant, For what can a human being rationally hope? It offers a detailed commentary on Kant's seminal work, Religion Within the Limits of Reason Alone, as well as an original development of the logic of three of Kant's basic ideas: ambivalence, ignorance, and hope. Sophisticated analytic techniques, including symbolic logic, are applied to this conceptual matrix. The result is a striking case for the transformation of world society into a Kingdom of Ends of individuals and a peaceful League of Nations.